Design of a separation machine using pneumatic system combined with sieve vibration for removing parchment coffee from Robusta green coffee bean - W Limmun; T Chungcharoen (My University, 2020)
Abstract The hulling process for coffee bean extraction may not effectively release the bean from parchment. This might negatively affect the aroma or taste of coffee in the coffee beans roasting process. Consequently, the objectives of this work were to design and construct a machine for separating parchment coffee from Robusta green coffee bean using a pneumatic separation system combined with sieve vibration. The performance of the separation machine was investigated under different operating conditions such as air velocity, vibration frequency, and the angle of sieve inclination. The samples were fed into the machine at a feed rate of 20 kg/h. The testing conditions were set at air velocities of 2 to 4 m/s, vibration frequencies of 36 to 40 Hz, and sieve inclination angle of 4° to 8°. The results showed that the purity and separation efficiency of parchment increased with increasing air velocity. Conversely, decreasing vibration frequency and sieve angle increased the purity and separation efficiency. The appropriate conditions for parchment coffee separation from Robusta green coffee bean using a pneumatic-sieve vibration system were 4 m/s air velocity, 36 Hz vibration frequency, and 8° sieve angle with the highest overall effectiveness of 92%.
Keywords: Sieve (category theory); Parchment; Roasting; Coffee bean; Agricultural Engineering and Mechanization